IMPROVING COMMUNITY AWARENESS IN NEW NORMAL APPLICATION THROUGH EXTENSIONS AT PHARMACEUTICAL WONOREJO SRAGEN - Rita Septiana (ABDIPRAJA (Jurnal Pengabdian kepada Masyarakat), 2021)
Until now, the Covid-19 pandemic was still a problem and limits various community activities such as work, study, and worship, as well as socializing / activities. The government's effort to keep moving various sectors, be it social, cultural, economic growth so as not to experience a slowdown, industry running and people not losing their income is by introducing new habits of life or what was called a new normal. With the enactment of the new normal, we begin to carry out activities outside the home while adhering to health protocols that have been regulated by the government, namely wearing masks when leaving the house, washing hands frequently with soap, and maintaining distance and avoiding crowds. The service activity entitled "New Normal Counseling in the Context of Preventing Covid-19 Transmission to Visitors at the Wonorejo Pharmacy, Sragen" aims to provide information and additional knowledge to the public regarding steps that can be taken in the new normal era. The target of the activity was people who come to the Pharmacy and were willing to participate in this activity. Activities carried out in the form of distributing brochures and providing information directly to people who visit the pharmacy. The service activities were carried out for 2 days, namely on Saturdays and Sundays, 10-11 October 2020 with 19 participants. With the implementation of this activity, it was hoped that the community will be able to continue their activities safely during the current pandemic. The result of this activity was increasing public awareness to adopt a new normal lifestyle, which will help government programs to break the chain of spreading the Covid-19 infection.